Validation of a food frequency questionnaire in assessing the omega-3 polyunsaturated fatty acids intake for Malays and Chinese elderly in Malaysia - Lai, Kuan Lee; Suzana Shahar,; Noor Aini Mohamad Yusoff,; AI-Vyrn, Chin (Universiti Kebangsaan Malaysia, 2013)
Omega-3 polyunsaturated fatty acids (PUFAs) is crucial to prevent a wide range of chronic diseases from a global view point. However, no suitable dietary assessment tool is available for usage among Malaysian population. The present study aimed to evaluate the validity of interviewer-administered semi-quantitative Food Frequency Questionnaire (FFQ) for assessing the omega-3 PUFAs intake among the Malays and Chinese elderly individuals in Klang Valley, Malaysia. Thirty-seven elderly people (54.1% women and 45.9% men), aged 60 years and above, were recruited from a community setting. Omega-3 PUFAs intake for the past one month was assessed using a 45-food item FFQ and validated against 3 days Food Record (FR). Wilcoxon signed rank test indicated no significant mean intake difference between two assessment methods. Significant correlation was found for total omega-3 PUFAs (r=0.926), α-linolenic acid (ALA) (r=0.745), eicosapentaenoic acid (EPA) (r=0.579) and docosahexaenoic acid (DHA) (r=0.912). Bland-Altman analysis exhibited no apparent systematic bias between the two methods for total omega-3 PUFAs intake, while quartile analysis classified 73% subjects assigned into the same quartile. Conclusively, the newly-developed FFQ yielded a reasonable validity in the tested population and provided a convenient means to estimate omega-3 PUFAs intake within healthy Malays and Chinese elderly individuals. Further study to evaluate its validity and reproducibility for different age groups is required.